Kinematic Comparison of Feint Maneuver between Dominant and Non-Dominant Legs and its Relationship with Anterior Cruciate Ligament Injuries in Female Professional Handball Players - Saeide Ilaghi-Hosseini; Fariborz Mohammadipour; Mohammadreza Amir-Seyfaddini (Vesnu Publications, 2018)
Introduction: Changing the direction of the body in fast moving movements is a matter of injury, which is of special importance in the injury mechanism of anterior cruciate ligament (ACL). The present study investigated the kinematic comparison of feint maneuver between dominant and non-dominant legs and its relation with anterior cruciate ligament injuries injury. Materials and Methods: In this study, 18 professional female handball players were selected in a targeted and convenience way. The subjects, after attaching the markers, ran for 3 meters and when arrived to marked location on the ground, performed the feint maneuver with their dominant leg and passed the bar. Then, performed the same action with their non-dominant leg. Raw data processing was implemented using Cortex software. Then, the variables of the knee joint (flexion/extension and valgus/varus) entered the SPSS software; and the Shapiro-Wilk test was used to evaluate the normality of the data. Lyon and dependent t tests were used for homogeneity and intragroup comparison, respectively. The significance level was considered at less than 0.05. Results: The changes in flexion (P = 0.346) and extension (P = 0.322) of knee joint were not significant between dominant and non-dominant legs; but the changes in valgus (P = 0.001) and varus (P = 0.001) of knee joint were significantly different between the dominant and non-dominant legs. Conclusion: The results of this study will help to understand the risk factors of kinematics in risky situations better, and thus can teach the correct way of performing techniques to athletes exposed to high-risk situations. It is better to use protective instruments such as brace or kinesiotape while doing this techniques.